Biodiesel Dari Biji Buta-Buta (Hura Crepitans Linn) Dengan Katalis Ni/Nza - Tresia Monika Natalia Sinaga; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Indonesia is one of the oil producing country in the world but is still importing fuel oil (BBM) for meet the fuel needs in various sectors. Therefore, an alternative is needed to meet these needs. Among them is to produce biodiesel from vegetable oil feedstock. One type of vegetable oil that can be used as a raw material is Hura crepitans Linn. This research is aimed to produce biodiesel from Hura crepitans Linn seed oil, to study effect of the metal content in the catalyst of Ni/NZA to biodiesel produced and to determine the best conditions of process of biodiesel and then characteristics of biodiesel produced. The transesterification process was done at a temperature of 60oC, the weight of oil 50 grams, the catalyst 1%-weight of oil, reaction time variation of 1, 1.5 and 2 hour and mole ratio of oil to methanol 1: 6, 1: 9, 1:12 and catalyst NZA of 0% and 2%. The highest biodiesel result gives at experiment of 2% metal content oil to methanol mole ratio of 1: 9, for 1.5 hours i.e. 85.8%. Characterization of physical properties of biodiesel obtained, density of 0.885 gram/ml, 4.29 cSt kinematic viscosity, acid number 0.49 mg KOH / g sample, and the flash point 180oC respectively. Chemical components of biodiesel analysed with Gas Chromatography-Mass Spectroscopy (GC-MS) produce methyl linolelaidate 72,64%, methyl Oleic 19,08%, methyl stearate 2,2%, methyl palmitate 2,11% and methyl octadec-11-enoic 0,66% respectively. Keywords : biodiesel, catalyst Ni/NZA, Hura crepitans Linn, transesterification